2020
DOI: 10.15251/cl.2020.175.251
|View full text |Cite
|
Sign up to set email alerts
|

RAMAN SPECTRA AND ELECTRONIC FEATURES FOR NANOTUBES OF ZnSSeWURTZIOD: AB-INITIO

Abstract: The ternary alloy ZnSxSe1-x wurtziod can be designed by simulation of DFT when varies the contents of S and Se atom. Study change band gaps of alloy wurtziod and density state. Density functional theory considers of the best approximations which associated with accuracy to simulate the geometrical, electronic characteristics and lines active of Raman. The clusters Zn7S3Se4 wurtziods at nano limited that obtains from wurtzite structure, note that band gaps of alloys decrease with the previous results for ZnS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, this form of termination is merely a resource used for the finite theoretical–molecular study of these nanotubes because it has not been reported experimentally. The main nanotube endings that have been observed experimentally are closed caps with graphitic layers, caps coated with metallic particles or clusters, free caps with dangling atoms (highly reactive), and flat-cap nanotubes. However, these findings are limited almost solely to CNTs (mainly) and BNNTs. This suggests that AlPNTs, GaPNTs, and InPNTs may also have a closed-cap type termination.…”
Section: Introductionmentioning
confidence: 99%
“…However, this form of termination is merely a resource used for the finite theoretical–molecular study of these nanotubes because it has not been reported experimentally. The main nanotube endings that have been observed experimentally are closed caps with graphitic layers, caps coated with metallic particles or clusters, free caps with dangling atoms (highly reactive), and flat-cap nanotubes. However, these findings are limited almost solely to CNTs (mainly) and BNNTs. This suggests that AlPNTs, GaPNTs, and InPNTs may also have a closed-cap type termination.…”
Section: Introductionmentioning
confidence: 99%
“…Alq3 has recently been found to boost the lifetime and efficiency of organic solar cells when used as buffering and/or dopant layers. There are two geometric isomers of Alq3: facial and meridional [6], [7]. The levels of LUMO and HOMO are anticipated for the two isomers that are expected to influence the injection barrier and act as charge carrier traps [8], [9].…”
Section: Introductionmentioning
confidence: 99%